MITIGASI PERUBAHAN IKLIM MELALUI PENGHIJAUAN DI RUANG TERBUKA HIJAU SMA NEGERI 3 MALUKU TENGAH - Sitanala, Merlin Renny; Tjoa, Marthina; Mardiatmoko, Gun (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2024)
The reforestation activity carried out at Senior High School 3 Central Moluccas Suli Village was by planting Ketapang kencana, pucuk merah, and mahoni seeds. Apart from that, durian dan pala seeds were also handed over for teacher and student to take home. PKM activities were carried out at senior high school based on the teamn’s proposal to carry out greening the school area. The proposal was well received by the school ang the team members carried out a survey to see the condition of the school and prepare seeds the were suitable for planting for school reforestation, and the seeds would be taken home by teachers and students to be planted on their respective land. Then the planting activity was caried out, information was also provided regarding climate change mitigation efforts through greening the school environment. The principal, teachers, and student were enthusiastic about planting the seeds provided by the team ang those who came home. They hope that by the reforesting the school area, they can create a beautiful and cool learning environment while also realizing climate change mitigation.